1) sinf(x).f '(x)dx= −cosf(x)+c


2) cosf(x).f '(x)dx=sinf(x)+c


3)
f '(x)
cos²f(x)
dx=tanf(x)+c



4)
f '(x)
sin²f(x)
dx= −cotf(x)+c




5)
sin(ax+b)dx= −
1
a
cos(ax+b)+c (a≠0)



6)
cos(ax+b)dx=
1
a
sin(ax+b)+c (a≠0)



7)
1
cos²(ax+b)
dx=
1
a
tan(ax+b)+c (a≠0)



8)
1
sin²(ax+b)
dx= −
1
a
cot(ax+b)+c (a≠0)




9)
tan(ax+b)dx= −
1
a
ln|cos(ax+b)|+c=
1
a
ln|sec(ax+b)|+c (a≠0)





10)
cot(ax+b)dx=
1
a
ln|sin(ax+b)|+c (a≠0)




Not1:

1
a²-x²
dx=arcsin(
x
a
)+c (a≠0)




Not2:

1
a²+x²
dx=
1
a
arctan(
x
a
)+c (a≠0)